Pest management of sesame in Ethiopia: A review - Alemu, Zemedkun (2022)
Sesame is Ethiopia’s most significant oil crop, especially Tigray, Amhara, and some lowland Oromia, Somalia, and the Gambella region. Consequently, the crop is exposed to a wide range of insect pests feeding on leaves, flowers, pods, and seeds affecting sesame yields. This article review provides information on the biology, nature of the damage, and management methods of economically important sesame pests. Sesame webworm, Antigastra catalaunalis (Duponchel) is the most common and frequently encountered pre-harvest pest of sesame. Sesame seed bugs, Elasmolmus sordidus (Fabricus) is also the most serious under field and storage conditions. Gall fly, Asphondylia sesami (Felt) could become a severe insect issue because of sesame gall formation, and Indian meal moth, Plodia interpunctella (Hubner) is a critical stored pest and a significant challenging of crop sesame in Ethiopia. Reports on minor pests are also listed. This paper summarizes current knowledge on pest management strategies, including cultural, biological, and botanical methods, and pesticide applications. The information gathered here indicates that the bioecology, host range, host plant resistance, the occurrence of insecticide resistance, and the development of integrated pest management methods for economical insect pests need to be addressed.